ANALISA PEMODELAN GENERATOR MAGNET PERMANEN TIGA PHASA DENGAN SUSUNAN MAGNET ROTOR MENGIKUTI IPM – V - Hidayat, Rezi; Alfiansyah, Fahmi; Fadila, Afif; Syofian, Andi; Anugrah, Anggun; Putera, Perdana (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2024)
This article is a study analysis for converting an automotive alternator with a maximum output of 24 volts 100 A, into a three-phase permanent magnet generator by replacing the alternator rotor with a permanent magnet rotor. The arrangement of the magnets is similar to the arrangement of an Interior Permanent Magnet (IPM) rotor in a 12-pole V model. Analysis is carried out using COMSOL Multiphysics® software, modeling permanent magnet generators adapting the shape of the alternator and the shape and number of coils on the alternator stator are maintained (not changed). Finite Element Method simulation results using N52 Neodymium Magnets on the rotor, the output voltage amplitude is 4.5 volts with an AC frequency of 50 Hz (at a speed of 500 rpm). The AC waveform of the modified generator output is not purely sinusoidal.Keywords : Generator, Permanent Magnets, Finite Element Method, Neodymium